Formulation And Stability Of Gel Toothpaste With Sungkai Leaf (Peronema Canescens Jack) Extract And Na-Cmc Gelling Agent - Halimatussa’diyah, Halimatussa’diyah; Wahyuni, Rini; Fitria, Karin Tika (Jurnal Riset Kesehatan, 2024)
The Sungkai leaf (Peronema canescens Jack), which is rich in alkaloids, flavonoids, tannins, and phenolics, has long been used as a natural immune booster, particularly during the pandemic. With increasing concerns over the health risks of fluoride, such as dental fluorosis and systemic toxicity, the demand for natural alternatives in oral care has risen. This study aimed to formulate and evaluate the physical stability of a gel toothpaste containing Sungkai leaf extract by examining the effects of varying concentrations of Na-CMC (Sodium Carboxymethyl Cellulose) as a gelling agent. Using an experimental one-shot case study design, the physical stability of different concentrations of NaCMC (3%, 4%, 5%, and 6%) was assessed. Stability testing was performed on 5 sample formulations per concentration. The tests included organoleptic properties, homogeneity, pH, foam height, and viscosity over four weeks. The results showed that all formulations met the Indonesian National Standard (SNI No.12-3524-1995), with semi-solid consistency, distinctive Sungkai odor, and slightly bitter taste. The average pH ranged from 6.42 to 6.84, the foam heights were stable, and the viscosity increased with higher Na-CMC concentrations, confirming the stability of the formulation. These findings suggest that natural Sungkai leaf-based toothpaste could provide a promising alternative to traditional fluoride-based products, particularly in markets concerned about chemical ingredients in oral care products.